Relative risks of chronic kidney disease for mortality and end-stage renal disease across races are similar. - Wen, Chi Pang; Matsushita, Kunihiro; Coresh, Josef; Iseki, Kunitoshi; Islam, Muhammad; Katz, Ronit; McClellan, William; Peralta, Carmen A; Wang, Haiyan; de Zeeuw, Dick; Astor, Brad C; Gansevoort, Ron T; et al. (Kidney Int, 2014)
Some suggest race-specific cutpoints for kidney measures to define and stage chronic kidney disease (CKD), but evidence for race-specific clinical impact is limited. To address this issue, we compared hazard ratios of estimated glomerular filtration rates (eGFR) and albuminuria across races using meta-regression in 1.1 million adults (75% Asians, 21% Whites, and 4% Blacks) from 45 cohorts. Results came mainly from 25 general population cohorts comprising 0.9 million individuals. The associations of lower eGFR and higher albuminuria with mortality and end-stage renal disease (ESRD) were largely similar across races. For example, in Asians, Whites, and Blacks, the adjusted hazard ratios (95% confidence interval) for eGFR 45-59 versus 90-104 ml/min per 1.73 m(2) were 1.3 (1.2-1.3), 1.1 (1.0-1.2), and 1.3 (1.1-1.7) for all-cause mortality, 1.6 (1.5-1.7), 1.4 (1.2-1.7), and 1.4 (0.7-2.9) for cardiovascular mortality, and 27.6 (11.1-68.7), 11.2 (6.0-20.9), and 4.1 (2.2-7.5) for ESRD, respectively. The corresponding hazard ratios for urine albumin-to-creatinine ratio 30-299 mg/g or dipstick 1+ versus an albumin-to-creatinine ratio under 10 or dipstick negative were 1.6 (1.4-1.8), 1.7 (1.5-1.9), and 1.8 (1.7-2.1) for all-cause mortality, 1.7 (1.4-2.0), 1.8 (1.5-2.1), and 2.8 (2.2-3.6) for cardiovascular mortality, and 7.4 (2.0-27.6), 4.0 (2.8-5.9), and 5.6 (3.4-9.2) for ESRD, respectively. Thus, the relative mortality or ESRD risks of lower eGFR and higher albuminuria were largely similar among three major races, supporting similar clinical approach to CKD definition and staging, across races.
Keywords: Adult; African Continental Ancestry Group; Aged; Aged, 80 and over; Albuminuria; Asian Continental Ancestry Group; Cardiovascular Diseases; Cohort Studies; Creatinine; European Continental Ancestry Group; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Male; Middle Aged; Odds Ratio; Renal Insufficiency, Chronic; Risk Factors